The Rice miR396-GRF-GIF-SWI/SNF Module: A Player in GA Signaling - Lu, Yuzhu; Zeng, Jia; Liu, Qiaoquan (Frontiers in Plant Science, 2022)
Rice Growth-Regulating Factors (GRFs) were originally identified to be gibberellin (GA)-induced, but the nature of GA induction has remained unknown because most reports thereafter focused on revealing their roles in growth-promoting activities. GRFs have the WRC (Trp, Arg, Cys) domain to target DNA and contain QLQ (Gln, Leu, Gln) domain to interact with GRF-Interacting Factor (GIF), which recruits ATP-dependent DNA translocase Switch/Sucrose Nonfermenting (SWI/SNF) for chromatin remodeling. Both GRFs and GIFs exhibit transcriptional activities but GIFs lack a DNA-binding domain. So, GRFs act like a navigator in the GRF-GIF-SWI/SNF complex, determining when and where the complex should work on. The levels of most rice GRFs can be sensitively regulated by miR396, which responds to many developmental and environmental factors. Recent clues from several studies highlight the original question how GRFs participate in GA signaling. DELLA protein plays dual roles in controlling the level of GRFs by regulating the level of miR396 and interacting with GRFs. Here we address the question why this complex plays an essential role in controlling plant growth focusing on the action of GA signaling pivot, DELLA.